(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2003)
It has been shown that after the recovery of nitrogene nutrition of starved yeasts the amount of water soluble proteins sinthesied by endogene nitrogene source is 2 times higher than the amount of proteins sinthesied by exogene nitrogene source.